NGHIÊN CỨU CHẾ TẠO MÀNG NIKEN/VONFRAM TRÊN NỀN ĐIỆN CỰC THÉP BẰNG PHƯƠNG PHÁP ĐIỆN KẾT TỦA - Sén, Trịnh Xuân; Hùng, Phạm Đức; Hoàn, Nguyễn Xuân (Vietnam Journal of Chemistry, 2012)
Nickel-tungsten films on the steel substrate were prepared by electrodeposition technique using citrate-containing baths at room temperature.¶ These films were deposited using conditions: {NiSO4 0,025M + Na3C6H5O7 0.025M + Na2WO4 0,05M}, pH = 7 - 8,  current densities I = 5 ÷ 35 mA/cm2, and the deposition time t = 60 minutes. The morphology and the composition of nickel-tungsten  films  were characterizied on the scanning electron microcopy (SEM) attached an energy dispersive spectroscopy (EDS).¶ The phase compositions were also identified by X rays diffraction technique.¶ The results shows that the present of tungsten on the films in some kinds of Ni(W), Ni4W and these films have good electrochemical property in KOH medium.